MENINGKATKAN PENGUASAAN MUFRADAT BAHASA ARAB MELALUI MEDIA PERMAINAN DAN LAGU - rahma, rahma (IAIN Parepare, 2023)
learning Arabic is often one of the most frightening lessons for students in schools and madrasas. Many of them do not like it when they get Arabic lessons. Even though the existence of Arabic is very important in the Islamic world. However, in this case there needs to be a change in learning. One of them is the learning method used must be changed to foster students' interest in learning Arabic. And when they are interested in learning Arabic, indirectly they will be able to participate in learning happily without any elements of coercion and pressure. Thus, the process of learning Arabic will take place according to plan and be able to be absorbed by students easily and pleasantly.